PROFIL KETERLIBATAN ORANG TUA DALAM PENDIDIKAN ANAK USIA TK - Mukti Amini (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
This study aimed at obtaining an overview of demographic data (education and employment) of the parents of kindergarten children, the parental involvement in the kindergarten activities and in educating their children at home. As an exploratory research with descriptive analysis, the study was conducted in the school year of 2013/2014 in Pamulang and Serpong, Sub District of South Tangerang, Banten, where 238 parents were participaed as the subjects of the research. The finding of the research showed, in terms of education and employment many parents are potential enough to take part in child care. The involvement of both parents both in the kindergarten and at home is pretty good, but needs to be improved, especially in educating their children at home everyday to be independent. The parents are also needed to persuade to be volunteers in the kindergarten. Therefore, further research is recommended to identify appropriate strategies to make the parents more involved in their children’s education.